DESKRIPSI MOTIVASI BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA PADA MATERI MATRIKS DI KELAS XI IPS SMA NEGERI 5 PADANG - Livia Gustianingsih (Jurnal Edukasi dan Penelitian Matematika, 2020)
Learning motivation is the one of supporting factor that students’ success in learning mathematics. Good students motivation can make students have confidence and a sense of respect in the learning environment on the other hand low motivation will reduce the students’ confidence so that it affects students learning outcomes. The purpose of this study was to determine the description of student’ motivation at XI IPS SMA Negeri 5 Padang in learning mathematics on matrix material.Keywords — Learning Motivation of Mathematics.